Focus group discussion and interview: some basic guidelines - Mokhtar, Nor Zainiyah Norita; Mohd Ismath, Nurul Hanilah (Perbadanan Kota Buku, 2020)
This chapter aims to share the use of focus group discussion (FGD) as one adoptable technique for qualitative research. It also discusses the Islamic perspective of syuraa’ which shares the same characteristics and objective of focus group discussion and also give insights on what role should the researcher play when conducting a focus group discussion. It is also important to highlight that no discussion or finding of this study will be included in this chapter. The chapter aims to only share the use of FGD and Syura as a methodology in a qualitative study.